Lexical Verbs in Malaysian University English Test Argumentative Essays: A Corpus-based Structural Analysis - Anita Kanestion; Manvender Kaur Sarjit Singh; Sarimah Shamsudin; Hishamuddin Isam; Naginder Kaur; Gurmit Singh Pertap Singh (International Review of Management and Marketing, 2016)
Argumentative writing is regarded as an essential form of written discourse in Malaysia, specifically in Malaysian University English Test (MUET). Accordingly, there are numerous studies on argumentative essays which demonstrate the increased interest in linguistic features. Conversely, limited studies have been conducted on the written discourse of the MUET argumentative essay at pre-university level. For this purpose, using a compiled representative learner corpus, a preliminary study is conducted to investigate the linguistic features; lexical verbs used in Band 5 and Band 3 argumentative essays produced by students of a pre-university college in Malaysia. Subsequently, the lexical verbs utilized in the respective essays were compared. As a descriptive analysis and corpus-based study, the use of lexical verb forms was examined via a computer-assisted corpus analysis, for short (CACA), reflecting the learners' knowledge of applying this linguistic constituent into their written essays. Albeit, this analysis revealed that both Band 5 and Band 3 essays employed four types of lexical verbs, namely past tense (VVD), -‘ing' form (VVG), past participle (VVN) and –s form (VVZ),  it was apparent that the lexical verb form of past tense (VVD) was underused by both groups (11 and 20 occurrences respectively). Surprisingly, both groups  had avoided the base form of lexical verb (VVO) in their essays. Thus, the findings of this study might render some pedagogical implications for both teachers and learners, especially in writing argumentative essays, and ideas for future research.